The Nag Hammadi story from the discovery to the publication - Robinson, James M. 1924- (Nag Hammadi and Manichaean Studies, 2014)
The Nag Hammadi Story is not a history of research in the usual sense of a Forschungsbericht , which would report on the massive amount of scholarship that has been devoted to the content of the Nag Hammadi Codices for more than a half-century. Rather it is a socio-historical narration of just what went on during the thirty-two years from their discovery late in 1945, via their initial trafficking, and then the attempts to monopolize them, until finally, through the intervention of UNESCO, the whole collection of thirteen Codices was published in facsimiles and in English translation, both completed late in 1977.